Theoretical study of forbidden unique and non-unique beta decays of medium-heavy nuclei - Soukouti, Nael (2015)
This Master's Thesis concerns using the quasi-particle random phase approximation model in the study of β decay. The study is done for the transition from the 2₁¯ state of odd-odd nuclei to the isobaric neighbour's (even-even nuclei) ground state and some low-lying excited states. The mass numbers of the studied nuclei are A=72, 74, 76, 78, 82, 84, 86, 88, 92, 94, 122, 124, 126, 132. The computed comparative β decay half-lives log(ft) values are compared with the experimental results.